Adipofascial radial artery perforator flap interposition to treat post-traumatic radioulnar synostosis in a patient with head injury. (27th February 2015) - Samson, Deepak; Power, Dominic; Tan, Simon
Abstract : We report this 47-year-old man who presented with polytrauma following a fall from a roof in March 2011. He sustained a head injury and a complex, comminuted forearm fracture. He underwent an open reduction and internal fixation of the fracture at the time of injury, but later developed a rigid type 2 diaphyseal radioulnar synostosis, with loss of forearm rotation. Synostosis excision and a radial artery perforator-based adipofascial interposition flap to prevent recurrence has resulted in a good functional outcome and no recurrence at 2.5 years follow-up.